الحسن الصباح ودورة في الحركة الباطنية - , م د. رحمن منصور حسين (Thi Qar Arts Journal, 2021)
Hassan Al-Sabah was born in the city of Qom, one of the first centers of Arab settlement in the ancient country of Iran, and one of the strongholds of the Shiites. His father was a Twelver Shiite. He was displaced from Kufa in Iraq. His exact date of birth is not known, but it is possible that he was born in the middle of the eleventh century. During his childhood, his father moved to Al-Rayy (which is currently the city of Tehran), where he received his religious studies. Al-Rayy was a center for the activity of Ismaili preachers since the ninth century . Hassan Al-Sabah completed his education, and events took place that led to his going to Cairo, where one of the stories mentioned by a number of historians says that Hassan Al-Sabah, the poet Omar Khayyam and Minister Nizam Al-Malik were classmates and taught by one teacher. Hassan Al-Sabah refused to work in any position in the remote regions, and sought a great job at the court. With this desire, he soon became a candidate for the ministry and a dangerous competitor to the king's own regime. Thus, the minister plotted an intrigue against him and was able to degrade him before the Sultan. As a result, Hassan Al-Sabah fled to Egypt feeling disappointed, and there he began preparing for his revenge. He barricaded himself in  Al Maut castle and formed of the Assassins Squad. This group and its remarkable founder, Hassan Al-Sabah, set out to establish a network of fortresses that extended from Afghanistan and the borders of India in the east to the coast of the Mediterranean in Syria in the west. The Assassins stabbed dozens of princes and leaders with their daggers and spread terror in the hearts of the Abbasid rulers, who assassinated two of them, and their daggers reached the chests of many important ones. He is considered one of the most dangerous leaders of the esoteric groups and his most dangerous Nizari group. The Sheikh of the Mountain, Sayyid Hassan Al-Sabah, died on May 23, 1124 AD in the Al Maut castle.